ANALISIS DERAJAD KONSOLIDASI PADA PERBAIKAN TANAH DENGAN METODE PRE-FABRICATED VERTICAL DRAIN (PVD) PADA PROYEK PEMBANGUNAN JALAN TOL SEMARANG – DEMAK PAKET 2 - Hastari Dita Ningrum; Ririn Anassari; Hartopo Hartopo; Totok Apriyanto (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2022)
Soft soil is a type of soil that has low shear strength, small coefficient of permeability, compressibility and low soil bearing capacity. 1-D consolidation theory by Terzaghi (1925), assumes that during the consolidation process the value of the consolidation coefficient (Cv) is constant. Flow is only vertical direction. The analysis carried out is to know magnitude of decline and time required to achieve 90% consolidation. Quantitative data is used to analysis numerical data and calculated using existing formulas. Value of settlement using Terzaghi method and principle of normal consolidation is 1.68834 m. To achieve a degree of consolidation of 90% without PVD is 274350 days with a decrease of 1.5196 m. With triangular pattern PVD installation on distance of 0.9 m is 75 days with a large reduction of 1.523 m. Based on the result, time required to achieve a degree of 90% consolidation using PVD is onliy 75 days, while on same day without using PVD consolidation results are around 0.017%. This shows that PVD can speed up the time required for soil consolidation.